In-hospital and mid-term outcomes in patients reoperated on due to bleeding following coronary artery surgery (from the KROK Registry). (9th April 2019) - Knapik, Piotr; Knapik, Małgorzata; Zembala, Michał O; Przybyłowski, Piotr; Nadziakiewicz, Paweł; Hrapkowicz, Tomasz; Cieśla, Daniel; Deja, Marek; Suwalski, Piotr; Jasiński, Marek; Tobota, Zdzisław; Maruszewski, Bohdan J; et al.
Abstract: OBJECTIVES: Surgical re-exploration due to postoperative bleeding that follows coronary artery surgery is associated with significant morbidity and mortality. The aim of this study was to assess a relationship between re-exploration, major postoperative complications, in-hospital mortality and mid-term outcomes in patients following coronary surgery, on the basis of nationwide registry data. METHODS: We identified all consecutive patients enrolled in Polish National Registry of Cardiac Surgical Procedures (KROK Registry) who underwent isolated coronary surgery between January 2012 and December 2014. Preoperative data, major postoperative complications, hospital mortality and mid-term all-cause mortality were, respectively, analysed. Comparisons were performed in all patients, low-risk patients (EuroSCORE II < 2%, males, aged 60–70 years) and propensity-matched patients. The starting point for follow-up was the date of hospital discharge. RESULTS: Among 41 353 analysed patients, 1406 (3.4%) underwent re-exploration. Reoperated patients had more comorbidities, more frequent major postoperative complications, higher in-hospital mortality (13.2% vs 1.8%, P < 0.001) and higher mid-term mortality in survivors ( P < 0.001). In the low-risk population, 3.0% of patients underwent re-exploration. Reoperated low-risk patients and propensity-matched patients also had more frequent major postoperative complications and higher in-hospital mortality, but mid-term mortality in survivors was similar. In a multivariable analysis, re-exploration was an independent predictor of death and all major postoperative complications. CONCLUSIONS: Surgical re-exploration due to postoperative bleeding following coronary artery surgery carries a high risk of perioperative mortality and is linked to major postoperative complications. Among patients who survive to hospital discharge, mid-term mortality is associated primarily with preoperative comorbidities.